Ideal Leadership in the Era of the Millennial Generation - Nugroho, Adi; Martono, S; Rokhman, Fathur; Handoyo, Eko; Suharini, Erni (Universitas Negeri Semarang, 2024)
Leadership is an intriguing topic that is essential for every generation. This implies that effective leadership necessitates a leader with strong character, the ability to lead, and the capacity to comprehend the changes and advancements that occur with time. As times change, new leaders emerge in response to the demands and circumstances of their environment. The leadership of the millennial generation is a critical challenge in contemporary society. As a result, this study aims to describe the ideal leadership traits for the millennial generation. The goal is to examine leadership theories and types, millennial characteristics, and ideal leadership traits for the millennial generation. This research is a literature study that involves gathering data from theoretical sources relevant to ideal leadership characteristics for the millennial generation. Leadership is a crucial component of the management process and is required in all types of organizations. Leaders plan and organize available resources by influencing and directing others to achieve optimal employee performance. Leadership success is influenced by the leadership style employed and employee satisfaction. Becoming a good leader for the millennial generation and beyond is a critical challenge. However, a good leader should also possess integrity, honesty, and loyalty to the interests of the people. Millennial leadership must foster the independence and entrepreneurial spirit of the millennial generation. Nation-building must have independence and entrepreneurship as its core foundations.